(untitled) (Journal of Comparative Social Work, 2008)
The significance of social capital, including social trust, has in recent decades been acknowledged by many scholars across different disciplines as a key resource. This has led to many studies and scientific articles investigating this topic. Few studies, however, have focused upon social trust within marginalised groups. This study is based upon data gathered from one of the larger research projects investigating the vulnerable recipients of voluntary welfare assistance in Norway. The aim of the study is to investigate the level of social trust in a sample of 80 recipients of welfare assistance within two large voluntary welfare organisations in the capital city of Oslo, Norway. In particular, the study will explore whether and to what degree the level of social trust can be explained by conditions experienced while growing up and as an adult. Results indicate that adult life experiences, such as drug abuse and life satisfaction are the most important explanatory variables. However problems experienced while growing-up seems to be indirectly related to social trust. The results of the study highlight the significance of acknowledging processes of marginalisation in socially vulnerable groups, such as drug users and children experiencing problems growing up.